A Comprehensive, annotated, and indexed bibliography of the modern scholarship on Fakhr al-Dīn al-Rāzī (544/1150 - 606/1210) - Janos, Damien. (Leiden ; Boston)
xviii, 242 sayfa
Keywords: “The study of Islamicate intellectual history has witnessed a rapid growth of scholarship on post-classical thinkers and especially on Fakhr al-Dīn al-Rāzī (d. 1210 CE), one of the leading theologians and philosophers of his time. However, there is presently a lack of methodological tools and reference works in Rāzī studies. This book is the first bibliographical work entirely devoted to this thinker. It surveys the modern historiography on Rāzī from the nineteenth century onward and includes more than 1000 specialized entries written in European languages, Arabic, Persian, and Turkish. The bibliography also provides a preface, an introductory essay, annotations to the entries, and various indices to help students and experts navigate the complex field of Rāzī studies“ --